Acoustic Survey on Habitat Use and Activity Patterns of Insectivorous Bats in a Riverine Forest at Gunung Mulu National Park, Sarawak, Malaysia - McArthur, Ellen (Universiti Malaysia Sarawak (UNIMAS), 2019)
Bats are keystone species that perform important ecosystem and economic services and are, therefore, an important fauna to be monitored. Acoustic monitoring with ultrasonic detectors has emerged, in recent years, as an essential tool to quantify the activity of echolocating insectivorous bats and identify key habitats used by them for commuting and foraging. However, only few acoustic studies have been conducted in the tropical forests of Southeast Asia. The objectives of this study are to build an echolocation call library that can be used to identify insectivorous bats through acoustic recordings; identify which habitats are used, by the various species of echolocating bats, for commuting and foraging; determine the timing of activity and some of the factors that may contribute to differences in activity within a riverine forest, dominated by karst outcrops, at Gunung Mulu National Park, Sarawak. Between 2014 and 2017, insectivorous bats were trapped at Gunung Mulu National Park and echolocation calls were recorded from a total of 503 individuals, representing 31 species. Results from discriminant function analysis indicated that the majority of cave roosting insectivorous bats could be readily distinguished from their calls. Acoustic sampling was conducted in a 4 sq. km area of riverine forest at Gunung Mulu National Park, for a total of 135 sampling nights, between May 2016 and May 2017. Activity patterns were compared between three rivers of different width, adjacent trails and forest interior and treefall gaps of various sizes. Five species in the family Rhinolophidae, six species of Hipposideridae, Myotis species, Chaerephon plicatus, Miniopterus australis and Emballonura species, which made up 95% of recordings, could be identified from their echolocation calls. Analysis of full night recordings showed that 84% of total bat activity was detected at rivers, 10% at forest gaps, 5% on trails and 1% in forest interior. Most species recorded were detected more often at rivers than in other habitats. Results indicated that activity at rivers was positively influenced by distance to karst, rather than by river width. Activity at forest gaps was positively influenced by gap width and not significantly affected by distance to karst. Acoustic sampling, although challenging to conduct in a megadiverse tropical environment, is proving to be an effective method in providing information about the ecology of insectivorous bats. This study also highlights the importance of rivers as critical habitats for foraging insectivorous bats in a tropical karst environment.